The Character of Legal Products of the Job Creation Law Related to Licensing Simplification - Rahmatika, Dana (PALAR (Pakuan Law review), 2025)
AbstractSimplifying the business licensing process is one of the main focuses in Law No. 11/2020 on Job Creation to boost economic growth and attract investment. However, the implementation of this policy faces various challenges, including overlapping regulations, difficulties in implementing the OSS system, and neglect of environmental protection. This research examines the issue of licensing simplification based on Mahfud MD's political theory of law, which distinguishes between democratic political configuration and responsive legal products. The results of the study show that the Job Creation Law is more inclined towards conservative and elite legal characters, which are more concerned with the ease of investment than environmental impacts and public participation. In addition, the drafting process is considered less transparent and does not adequately involve the community, thus creating a legal product that is not responsive to the needs of the people. The simplification of licensing in the Job Creation Law needs to be improved to be in line with the principles of democracy and social justice that form the basis of the Indonesian state. Keywords:  Legal Product Character, Legal Politics, Job Creation Law.